2014
DOI: 10.1007/s11655-014-1769-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of T-helper 17 cells and signal transducers in patients with psoriasis vulgaris of blood-heat syndrome and blood-stasis syndrome

Abstract: Cytokines in serum and signal transducers in the psoriatic lesions alter with various CM syndromes of psoriasis. The results provide scientific basis for the treatment based on syndrome differentiation of CM in treating psoriasis vulgaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Comprehensive whole-genome screening of the transcriptome has previously suggested that disease-specific mechanisms are distinguishable [ 30 32 ]. Syndrome differentiations could be characterized by the expression of different genes [ 17 22 ]. Using microarray profiling and bioinformatics to investigate the gene expression patterns of BSS could illuminate the pathological mechanisms of BSS and provide potential biomarkers for clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive whole-genome screening of the transcriptome has previously suggested that disease-specific mechanisms are distinguishable [ 30 32 ]. Syndrome differentiations could be characterized by the expression of different genes [ 17 22 ]. Using microarray profiling and bioinformatics to investigate the gene expression patterns of BSS could illuminate the pathological mechanisms of BSS and provide potential biomarkers for clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA is an endogenous, non-protein coding, single-stranded, small RNA that is generally regarded as negative regulator of gene expression by inhibiting translation and/or promoting mRNA degradation [ 16 ]. Research has shown that the expression of mRNA and miRNA varies in different syndromes of diseases [ 17 22 ], and the patterns and interactions between mRNA and miRNA may provide an approach to estimate the syndrome differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines secreted by T cells was reported to form complex networks in psoriasis and the imbalance of T helper (Th)1/Th2 cells may lead to psoriasis . It has also been found that Th17 cells interact with STAT3 and MAPK in psoriasis vulgaris and participate in the regulation of psoriasis . Whether the silencing of KRT16 gene affects Th1 and Th17 cytokines will be the focus of our next work.…”
Section: Discussionmentioning
confidence: 99%
“…38 It has also been found that Th17 cells interact with STAT3 and MAPK in psoriasis vulgaris and participate in the regulation of psoriasis. 39 Whether the silencing of KRT16 gene affects Th1 and Th17 cytokines will be the focus of our next work.…”
Section: Discussionmentioning
confidence: 99%
“…ere are currently no fundamental drugs or treatment methods for psoriasis, which means that it is intractable and shows chronic recurrence, sometimes over an entire lifetime. Additionally, irregular or overtreatment by doctors causes tremendous financial burden and psychological stigma to patients and their families, seriously affecting quality of life [9,10]. erefore, a safe, effective, and economical treatment that results in a low recurrence rate is the most important goal for clinicians and researchers.…”
Section: Introductionmentioning
confidence: 99%